Eficiência das instituições públicas: o caso da lei de trânsito brasileira - Marcos Mendes (Economia Aplicada, 2002)
Microeconomic theory shows that it is Pareto-inefficient to deliver public goods through private markets. Institutions - especially laws - are necessary to provide public goods like clear air, traffic security and fiscal stability. However law compliance depends on a benefit-cost evaluation made by the potential law-breaker, as shown by Becker (1968). This paper studies the efficiency of the Brazilian traffic law, effective in 1998, which objective was the mortality reduction in traffic related accidents. It is shown that this reduction was only temporary. If this evidence is an indicator of low credibility of social rules in Brazil, valid to situations like fiscal responsibility and patent protection so, according to the new institutional economics, there are negative incentives to investment and growth in the long run.